Rancang Bangun Sistem Proteksi Otomatis pada Generator Turbin Gas dari Arus Berlebih dan Drop Tegangan Guna Meningkatkan Keandalan Operasional - I Made Dody Permana; Antonius Edy Kristiyono; Achmad Dhany Fachrudin (Pusat riset dan Inovasi Nasional, 2026)
Gas turbine generators play an important role in providing electrical energy, especially in the maritime sector, but they are vulnerable to disturbances such as overcurrent and undervoltage, which can cause equipment damage. This study aims to design and test an automatic protection system based on the ESP32 microcontroller with the INA219 sensor to detect current and voltage, as well as a relay as a circuit breaker. The method used is an experimental approach including static and dynamic testing, both with and without a 5W AC lamp load as a simulation of real loading conditions. Test results show that the average sensor reading error is 2.65% for current and 1.76% for voltage, which is still within the ±3% tolerance limit. The system is able to disconnect the load when any parameter exceeds the protection threshold, although there are slight inconsistencies in the relay response due to sensor reading fluctuations. In conclusion, this automatic protection system is proven to be 85% accurate and responsive in maintaining the operational reliability of the gas turbine generator, making it applicable as a preventive solution against electrical disturbances in marine environments.